The dynamics of food fraud: the interactions between criminal opportunity and market (dys)functionality in legitimate business - Lord, Nicholas (Criminology & criminal justice, 2017)
This article conceptualizes ‘food fraud’ by shifting analytical focus away from popular/policy conceptions foregrounding the centrality of organized crime towards understanding the factors that shape the organization of food frauds. We argue that food fraud, rather than being an ‘exogenous’ phenomenon perpetrated by externally organized (transnational) ‘criminal enterprise’, is better understood as an ‘endogenous’ phenomenon within the food system where legitimate occupational actors and organizations are in some way necessarily involved. Criminal opportunities arise under conducive conditions as part of legitimate actors’ routine behaviours. Our contention is that the common definition of food fraud is too prescriptive and fails to allow space to understand the role of different actors and their motivations. We analyse a case study in soft drinks, presenting the necessary role of legitimate, occupational actors within/between legitimate organizational settings and markets, and demonstrate how criminal behaviours can be concealed and disguised within ‘ready-made’ market and business structures.